SPATIAL ANALYSIS OF VOTING PATTERNS IN RESERVED CONSTITUENCIES: DELHI ASSEMBLY ELECTION, 2015 - Verma, Anupama (European Scientific Journal, ESJ, 2015)
Electoral geography is interested in the study of elections to understand spatial variations of political phenomena, which are deeply embedded with the environment occurring at the time of election and the people’s perception about various political parties. The voting behaviour of the electorates is greatly influenced by their perception existing at the time of elections. The voters perception about election’s environment and political parties are vary over one constituency to another constituency. Electoral geography viewpoint, the changing scenario of party competition and electoral behaviour of the electorate of Delhi is a very interesting problem area for study. The electoral behaviour largely influenced by the socio – economic conditions of geographical area. In 2013 Assembly election BJP tops Delhi and Aam Aadmi Party came out as a show-stopper. Aam Aadmi Party secured absolute majority in 2015 assembly election, winning 67 of the 70 seats and came out as a ruling party. Here attempt have been made to see the electoral participation and party competition in the reserved constituencies of Delhi. Attempt has been made to establish whether the location of a reserved constituency in a particular point of space is important or the reservedness of the constituency is important in predicting the electoral behaviour. For the analysis of voting data important indicators have been taken like to show the spatial distribution of seats won by various contesting parties’ areal structural approach were used. The results are depicted by means of choropleth maps. This gives a quick visual idea of the areal pattern of party stronghold. Beside that integrated approach applied to show the spatial structure of voting behaviour as revealed in election results. This is based on highly generalized voting data.